An Online Engagement Framework for Higher Education - Redmond, Petrea; Heffernan, Amanda; Abawi, Lindy; Brown, Alice; Henderson, Robyn (Online Learning, 2018)
Student engagement is understood to be an important benchmark and indicator of the quality of the student experience for higher education; yet the term engagement continues to be elusive to define and it is interpreted in different ways in the literature. This paper firstly presents a short review of the literature regarding online engagement in the higher education environment, moving beyond discipline-specific engagement. It then presents a conceptual framework which builds upon recurring themes within the literature, including students’ beliefs, attitudes, and behaviours. The framework was developed by adopting a constant comparison method to analyse the literature, and to search for and identify current and emerging themes. The framework identifies indicators for five key elements of online engagement, and the authors propose that the framework provides a guide for researchers and academics when exploring online engagement from a conceptual, practical and research basis. Finally, the paper provides recommendations for practice, outlining how the framework might be used to reflect critically upon the effectiveness of online courses and their ability to engage students.